Relationship Between Subclinical Cardiac Troponin I Elevation and Culprit Lesion Characteristics Assessed by Optical Coherence Tomography in Patients Undergoing Elective Percutaneous Coronary Intervention. (April 2015) - Lee, Tetsumin; Murai, Tadashi; Yonetsu, Taishi; Suzuki, Asami; Hishikari, Keiichi; Kanaji, Yoshihisa; Matsuda, Junji; Araki, Makoto; Niida, Takayuki; Isobe, Mitsuaki; Kakuta, Tsunekazu
<x xml:space="preserve">Abstract</x> Background— The prevalence of subclinical, cardiac troponin I (cTnI) elevation in stable patients undergoing elective percutaneous coronary intervention and its relationship to culprit lesion characteristics assessed by optical coherence tomography (OCT) are unknown. Methods and Results— We studied 206 native de novo culprit coronary lesions from 206 patients with stable angina pectoris who underwent OCT before elective percutaneous coronary intervention. Patients were divided into 2 groups according to the presence (cTnI group; n=47; 22.8%) or absence (non-cTnI group; n=159; 77.2%) of cTnI ≥0.03 ng/mL at admission. The clinical and OCT findings were compared between these 2 groups. No significant difference was found in the clinical presentation between the groups except for the serum C-reactive protein levels and presence of multivessel disease. By OCT, cTnI elevation was associated with the presence of thin-cap fibroatheromas, a greater lipid arc, and a longer lipid length. In a multivariable analysis, the presence of positive C-reactive protein levels (odds ratio, 4.38; 95% confidence interval, 1.90–10.08; P=0.001) and OCT-derived thin-cap fibroatheromas (odds ratio, 2.89; 95% confidence interval, 1.22–6.86; P=0.016) were independent predictors of cTnI elevation. Periprocedural myocardial injury, defined as postpercutaneous coronary intervention peak cTnI levels >1.0 ng/mL (5× the upper reference limit), occurred more often in patients with cTnI elevation at admission (cTnI group: 41% versus non-cTnI group: 18%; P=0.001). Conclusions— The presence of subclinical cTnI elevation at admission was not uncommon and was associated with OCT-derived unstable plaque morphology in patients undergoing elective percutaneous coronary intervention, and may help to identify patients with stable angina pectoris at high risk for periprocedural myocardial injury.